(untitled) ("Conference on Universal Science Research 2023", 2024)
Overall mortality after percutaneous coronary interventions ranges from 0.4 up to 1.9%. Among patients with acute coronary syndrome, in-hospital mortality rates for percutaneous coronary interventions are significantly higher and amount to 5-7%. Despite the constant improvement of the technology of percutaneous coronary interventions, the problem of their complications still remains extremely relevant. However, complications that arise in the early or late postoperative periods significantly reduce their clinical effectiveness.